Teaching about climate change in medical education: an opportunity - Janie Maxwell; Grant Blashki (SAGE Publishing, 2016)
Climate change threatens many of the gains in development and health over the last century. However, it could also be a catalyst for a necessary societal transformation to a sustainable and healthy future. Doctors have a crucial role in climate change mitigation and health system adaptation to prepare for emergent health threats and a carbon-constrained future. This paper argues that climate change should be integrated into medical education for three reasons: first, to prepare students for clinical practice in a climate-changing world; secondly, to promote public health and eco-health literacy; and finally, to deepen existing learning and strengthen graduate attributes. This paper builds on existing literature and the authors' experience to outline potential learning objectives, teaching methods and assessment tasks. In the wake of recent progress at the United Nations climate change conference, COP-21, it is hoped that this paper will assist universities to integrate teaching about climate change into medical education.